Gamification in Biomedical Sciences programme: wordsearch - Md. Akim, Abdah (Universiti Putra Malaysia Press, 2018)
Gamification in education may help students to recognize words mentioned in textbooks and lectures with ease. This can further assist students to memorize the words and its meanings. This method may assuage the fears of memorizing terminology. This book is the second book for Gamification in Biomedical Sciences Programme book series. It may be coupled with the first book, Crossword Puzzle, to strengthen the memorization and understanding of the subject matter. It is with great hope that both books will be of great value to those who want to pursue Biomedical Sciences.